Cellular response to PorA-Loop4-derived peptides of Neisseria meningitidis - Firdaus, Rininta (2019)
Neisseria meningitidis (the meningococcus) is a major meningitis-causing bacterium and is known for its ability to breach the blood-brain barrier (BBB). Meningococci bind to the Laminin receptor (LAMR) on the surface of the vascular endothelium, which is part of the BBB. In a previous study, the meningococcal surface proteins PorA and PilQ were identified as the bacterial ligands responsible for binding and, subsequently, the LAMR-binding moiety of PorA was localised to its fourth extracellular loop (PorA-Loop4). PorA preferentially targets the 37 kDa laminin receptor precursor (37LRP) rather than the 67 kDa laminin receptor form (67LR) on the cell surface. It was confirmed that the PorA:37LRP interaction is mediated by PorA-Loop4 as deletion of this loop abrogates recruitment of 37LRP under meningococcal colonies. Using a cyclised peptide corresponding to PorA-Loop4 from N. meningitidis MC58, the PorA-Loop4:37LRP interaction induced specific cellular responses in human brain microvascular endothelial cells (HBMECs) including G1-phase cell cycle arrest. The interaction of PorA-Loop4:37LRP was cytostatic, not cytotoxic. Flow cytometric analysis indicated that the treatment of HBMECs with PorA-Loop4 for 24 h caused a significant reduction of cells at S-phase and a corresponding increase in the G1 population.